Optimization of Coating Process from Cermet Powders by Plasma Spraying in Air - V. A. Okovity (Nauka i Tehnika, 2021)
The paper presents studies on the optimization of the process of applying coatings from cermet powders with different solid phase contents by plasma spraying in air to restore and harden parts of machines and mechanisms operating under adverse conditions. Such conditions are usually created in heavily loaded tribojoints when the mechanisms operate at a low speed of relative movement of surfaces during friction. At the same time, the destruction of the working surfaces is mainly due to the process of microcontact setting and subsequent detachment of the formed particles at their contact points. The application of special protective coatings with the required properties is possible with the manufacture of high-quality starting powder materials and optimization of the technology for their application. Such powders and powder compositions can be obtained by the method of agglomeration of a fine powder mixture with its subsequent high-temperature sintering. To identify the hardening mechanism of composite coatings made of cermet by gas-thermal spraying, important stages are the optimization of the deposition process parameters and the study of the properties of plasma coatings obtained in this case. When optimizing the technological parameters of plasma spraying of coatings, the utilization rate of the sprayed powder material has been taken into account as the main indicator of the process efficiency, the structure of the obtained layers, and the morphology of individual particles deposited on the polished surface. The paper provides data on the structural elements of sprayed materials for wear-resistant coatings obtained by plasma spraying at optimal conditions. Taking into account the processes that occur during the wear of tribological conjugations, the data indicate the existing prerequisites for the wear resistance of the studied composite coatings made of metal ceramics. Special wear-resistant coatings made of materials with a soft matrix hardened by solid inclusions Al2O3–TiO2–Ni–Cr–Al–Y are widely used in various industries. Based on the detailed analysis of the features of cermet plasma coatings, it can be stated that such powder compositions (complex oxides-metal component) are often used as wear-resistant plasma coatings. The research results can be taken into account in cases of application of wear-resistant plasma coatings made of metal-ceramics and compositions based on them, containing solid phases in the form of oxides, as well as the manufacture of a whole range of parts operating under conditions of intense wear.